Yttrium‐Catalyzed Synthesis of Bipyridine‐Functionalized AB‐Block Copolymers: Micellar Support for Photocatalytic Active Rhenium‐Complexes. Issue 19 (24th August 2018) - Adams, F.; Pschenitza, M.; Rieger, B.
Abstract: Herein, ortho ‐methylated bipyridines are introduced as initiators in 2‐aminoalkoxy‐bis (phenolate) yttrium complexes. For this C−H bond activation (ONOO) t Bu Y(CH2 TMS)(thf) (1 ) (TMS=trimethylsilyl) is reacted with the respective bipyridine to obtain complexes (ONOO) tBu Y(6‐Me2 bpy) (2 ) and (ONOO) tBu Y(6‐Mebpy) (3 ). Both complexes were tested first in rare‐earth metal‐mediated group‐transfer polymerization of 2‐vinylpridine (2VP). Complex 3 was further tested in block copolymerizations of 2VP and diethyl vinylphosphonate. The obtained initiator‐P2VP‐PDEVP‐block copolymers can selectively react with Re(CO)5 Cl at their bipyridine end‐group. The obtained rhenium functionalized block copolymers are able to self‐assemble to unimodal micelles in water, representing a possible carrier for hydrophobic metal containing complexes into cells. Furthermore, the Re‐block copolymers sustain activity in the photocatalytic homogeneous CO2 reduction and their performance exceed the catalytic activity of the analogue polymer‐free system [Re(CO)3 (6‐Mebpy)Cl] (4 ). Abstract : Versatile blocks : Bipyridine‐P2VP‐PDEVP‐block copolymers are synthesized via REM‐GTP. The bpy end‐groups can serve as ligands for metal complexation, which is shown by complexation of [Re(CO)5 Cl]. The obtained Re‐block copolymers can assemble as micelles as well as photocatalytically reduce CO2 .